1997
DOI: 10.1159/000218048
|View full text |Cite
|
Sign up to set email alerts
|

Human Bone Cells Stimulate the Growth of Human Breast Carcinoma Cells

Abstract: Human breast cancer cells were cultured together with their metastatic target, bone tissue, to analyze possible growth promotion effects. The coculture of human osteosarcoma cells (TE-85) with human mammary carcinoma cells (ZR-75.1) resulted in up to 8.4-fold stimulation of proliferation of the breast tumor cells. Cell contact of the two cultures was permitted through the channels of Nuclepore filters. However, physical contact turned out not to be necessary, since the proliferative stimulus was also mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
3
2
0
Order By: Relevance
“…Previous reports by Kallioniemi and Schöndorf showed that a greater percentage of metastatic patients with cerbB-2 overexpression had dominant visceral metastases instead of soft tissue and bone metastases (22,23). This is also in agreement with results obtained in cell culture by Goren, who showed that c-erbB-2-negative breast tumors had a propensity to develop bone metastases (24).…”
Section: Discussionsupporting
confidence: 93%
“…Previous reports by Kallioniemi and Schöndorf showed that a greater percentage of metastatic patients with cerbB-2 overexpression had dominant visceral metastases instead of soft tissue and bone metastases (22,23). This is also in agreement with results obtained in cell culture by Goren, who showed that c-erbB-2-negative breast tumors had a propensity to develop bone metastases (24).…”
Section: Discussionsupporting
confidence: 93%
“…This was further confirmed by the fact that the ER antagonist ICI182,780 did not interfere with the growth induced by OCM on ERC MCF-7 cells, indicating that osteoblast-secreted substances could rescue the growth of ERC breast cancer cells from estrogenic control. Our results are consistent with a previous report showing that conditioned medium collected from primary human osteoblasts cultures had a pronounced stimulatory capacity on some human mammary tumor cells (Goren et al 1997). A, MDA-MB-231 cells at 60% confluence were incubated for 24 h with phenol red-free DMEM, 5% charcoalstripped FCS before the addition of OCM (50% final concentration) for an additional 24 h. MCF-7 cells at 60% confluence were incubated for 24 h with phenol red-free DMEM, 5% charcoal-stripped FCS before the addition of E 2 (10 nM), OCM (50% final concentration), ICI182,780 (1 mM), or their combinations for an additional 24 h. Cells were harvested, total RNA was isolated and real-time RT-PCR was performed with 1 mg total RNA.…”
Section: Discussionsupporting
confidence: 94%
“…In a separate set of experiments, the cells were incubated with OCM in the absence or in the presence of anti-PDGF antibody which recognizes both PDGF-A and PDGF-B (Upstate, Charlottesville, NY, USA) or anti-TGF-b (Chemicon International, Inc., Temecula, CA, USA) neutralizing antibodies at 15 and 5 mg/ml concentration respectively. These concentrations are in the range reported previously for neutralization (Gorlach et al 2000, Dunker et al 2001. According to manufacturers' instructions, the antibodies concentrations should neutralize !10 ng/ ml PDGF and !1 ng/ml TGF-b in media.…”
Section: Cell Growth Characterizationsupporting
confidence: 82%
“…Liposomes, prepared using natural or synthetic lipids, mimic these naturally occurring vesicles and are attractive as delivery vehicles because of their unique ability to encapsulate hydrophilic molecules inside the aqueous lumen as well as hydrophobic drugs between the hydrophobic tails of the lipids. 1, 2 However, the lack of chemical flexibility and physical stability of conventional liposomes has limited their applications in drug delivery. These issues have led to a great deal of interest in polymer-based delivery approaches.…”
Section: Introductionmentioning
confidence: 99%